A Fatal Tyre Blast Injury: An Autopsy Case - Kumar, Rajesh; Sheikh, Nishat Ahmed (Nepal Journal of Epidemiology, 2022)
A 49-year-old man sustained an accidental injury when he was changing and inflating the tyre of a truck, and there was a sudden explosion of the truck tyre at the service station, which was by the roadside of the highway. With the pressure of air generated due to the exploding tyre, the victim was blown to around 6 feet away. He was declared dead on admission. The medico-legal examination was conducted, and death was determined to be multiple organ injuries [mainly head, chest, and abdominal injuries] caused by the shock wave produced due to tyre explosion. Tyre blast injuries are not so common. A meticulous post-mortem examination is fundamental in formulating and recording the pattern of traumatic injuries. Preventive occupational measures should be put in place.